Structures on the move: technologies of governance in transcultural encounter - Flüchter, Antje; Richter, Susan (Transcultural Research – Heidelberg Studies on Asia and Europe in a Global Context, 2012)
This book presents a new conceptual framework for comparative and entangled research on transcultural state formation. It examines concepts of statehood to provide conceptual tools to analyze the transcultural appropriation of governmental technologies